2018
DOI: 10.1016/j.wjorl.2018.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and depression in spasmodic dysphonia patients

Abstract: Objective/HypothesisExperts used to believe that spasmodic dysphonia (SD) was a psychogenic disorder. Although SD is now established as a neurological disorder, the rates of co-morbid anxiety and depression range from 7.1% to 62%. Our objective was to study the prevalence and risk factors associated with these mood disorders in SD patients.Study designRetrospective.MethodsSD patients who presented for botulinum toxin injections were recruited. Demographic data, Hospital Anxiety and Depression Scale (HADS), Voi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 31 publications
(73 reference statements)
1
7
0
Order By: Relevance
“…There was a hypothesis that SD patients in the past were associated with increased psychiatric conditions. 16 One previous study reported that high anxiety levels were associated with higher levels of patient-perceived hoarseness in adductor SD patients. 1 We examined whether psychiatric disorders would affect the success of injections.…”
Section: Discussionmentioning
confidence: 96%
“…There was a hypothesis that SD patients in the past were associated with increased psychiatric conditions. 16 One previous study reported that high anxiety levels were associated with higher levels of patient-perceived hoarseness in adductor SD patients. 1 We examined whether psychiatric disorders would affect the success of injections.…”
Section: Discussionmentioning
confidence: 96%
“…It is possible that increased functional connectivity between the caudate and the precuneus in UVFP patients reflects a heightened sense of self‐referential awareness, compared to healthy controls without dysphonia. It is also possible that this increased connectivity between the caudate and the precuneus is reflective of heightened anxiety found to be more common in patients with dysphonia, similar to patients with generalized and social anxiety disorders who also show increased connectivity between the precuneus and the caudate …”
Section: Discussionmentioning
confidence: 99%
“…Given that a recent study by Hu et al showed the prevalence of anxiety among this patient population to be around 15%, more research should be done to identify risk factors and protective measures to help patients acclimate to their condition. 14…”
Section: Discussionmentioning
confidence: 99%